1963
DOI: 10.1126/science.141.3575.48
|View full text |Cite
|
Sign up to set email alerts
|

Language and Thinking: Positive and Negative Effects of Naming

Abstract: Subjects instructed to think of novel shapes in terms of relevant names made fewer errors in recalling a serial ordering of the shapes, but more errors in solving a mental jigsaw puzzle and in drawing the shapes from memory, than subjects instructed to visualize the shapes without using words.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…One manipulation that has been found to enhance recognition memory for unfamiliar, meaningless, and complex stimuli is verbal labeling (e.g., Daniel & Toglia, 1976;Ellis, 1968;Ranken, 1963;Santa, 1975). In these experiments, a complex, random shape is associated with a verbal label, sometimes random as well (e.g., Daniel & Toglia's subjects associated polygons with colors), but often not (e.g., Santa used labels suggestive of the shapes in one of the conditions), and this association leads to better performance on a subsequent (mostly forced choice) recognition test.…”
mentioning
confidence: 99%
“…One manipulation that has been found to enhance recognition memory for unfamiliar, meaningless, and complex stimuli is verbal labeling (e.g., Daniel & Toglia, 1976;Ellis, 1968;Ranken, 1963;Santa, 1975). In these experiments, a complex, random shape is associated with a verbal label, sometimes random as well (e.g., Daniel & Toglia's subjects associated polygons with colors), but often not (e.g., Santa used labels suggestive of the shapes in one of the conditions), and this association leads to better performance on a subsequent (mostly forced choice) recognition test.…”
mentioning
confidence: 99%
“…During the past decade, however, more attention has been paid to analyzing the function of imagery in cognition, as Bartlett in 1932 had suggested (Neisser, 1967;Richardson, 1969;Paivio, 1971). Ranken (1963) and Paivio (1971) feel that imagery is useful for processing spatially oriented material and coding the figural properties of shapes or geometric designs, while language is more valuable for processing sequentially oriented material. Imagery as a mediator in cognitive processes has been studied by Paivio and others through paired associate learning.…”
mentioning
confidence: 99%
“…Ranken (1963) showed that visual imagery may be superior to verbal coding in recall of novel shapes. Ranken (1963) showed that visual imagery may be superior to verbal coding in recall of novel shapes.…”
mentioning
confidence: 99%
“…experimental evidence that, contrary to the usual assumption, the symbolic mode is not optimal for all experimental tasks. Ranken (1963) showed that visual imagery may be superior to verbal coding in recall of novel shapes.…”
mentioning
confidence: 99%